(3YgO ddSdWGf GdeDjO CHj GdaJM CMeO Hf Gdedc GdCTQa CHj GdfUQ EjfGds - (3GHf GdTMfI GdUZjQ , eMeO Hf eMeO Hf eMeO Hf eMehO Hf ZGRj GdKbaj GdMdHj, CHh GdaVd Hf CHj GdhdjO,J (B890 (3g` s
(3ChdgG (B:s
(3gPG YgO TQja JHSe KZQ QHjYg deG JfSe ai LeGOi s
(3BNQgG (B:s
(3hcGfJ GdHjYI GdeHGQcI jhe GdCQHYGA QGHY YTQ LeGOi GdChdi SfI NeS hSJjf hKeGfeGFI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B234 - (3U(B238s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B291 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs